Philosophy in children's literature - Costello, Peter R., 1971- (Lexington Books, 2012)
"This book seeks to join the ongoing, interdisciplinary approach to children's literature by means of sustained readings of individual texts by means of important works in the history of philosophy. Its inclusion of authors from both various departments--philosophy, literature, religion, and education--and various countries is an attempt to show how traditional boundaries between disciplines might become more permeable and how philosophy offers important insights to this interdisciplinary, critical conversation"--provided by publisher.